2016
DOI: 10.1103/physreve.94.052403
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of small myosin II ensembles from different isoforms to mechanical load and ATP concentration

Abstract: Based on a detailed crossbridge model for individual myosin II motors, we systematically study the influence of mechanical load and ATP concentration on small myosin II ensembles made from different isoforms. For skeletal and smooth muscle myosin II, which are often used in actomyosin gels that reconstitute cell contractility, fast forward movement is restricted to a small region of phase space with low mechanical load and high ATP concentration, which is also characterized by frequent ensemble detachment. At … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 37 publications
2
28
2
Order By: Relevance
“…The correlation between run length and dwell time is stronger than at 100 µM ATP with most myosin II filaments exhibiting persistent motion for up to 6 s (Pearson coefficient 0.57) and a loss of this correlation at longer dwell times (Pearson coefficient -0.18) ( Fig 3H). We emphasize that the myosin II filament motion is more persistent and faster at 10 µM ATP as compared to 100 µM ATP in agreement with recent theoretical studies (15,23). These results suggest that increased processivity and dwell time with decreasing ATP concentrations provides a molecular mechanism underlying the transition from a remodeling to a contractile acto-myosin network.…”
Section: Binding Dynamics Of Myosin II Filaments To Actinsupporting
confidence: 91%
See 3 more Smart Citations
“…The correlation between run length and dwell time is stronger than at 100 µM ATP with most myosin II filaments exhibiting persistent motion for up to 6 s (Pearson coefficient 0.57) and a loss of this correlation at longer dwell times (Pearson coefficient -0.18) ( Fig 3H). We emphasize that the myosin II filament motion is more persistent and faster at 10 µM ATP as compared to 100 µM ATP in agreement with recent theoretical studies (15,23). These results suggest that increased processivity and dwell time with decreasing ATP concentrations provides a molecular mechanism underlying the transition from a remodeling to a contractile acto-myosin network.…”
Section: Binding Dynamics Of Myosin II Filaments To Actinsupporting
confidence: 91%
“…Our approach allowed us to determine that a change in myosin II filament dwell times from τ1,100µM ATP = 1.23 s to τ1,10µM ATP = 3.7 s switches the acto-myosin network from a remodeling to a contractile state, and that myosin II filaments move faster and more processively at 10 µM ATP. This effect of ATP concentration on myosin II filaments under load provides evidence for predictions made by theoretical studies (15,23). Our observations indicate that the control of myosin dwell times could provide an ideal way for a biological system to switch between a remodeling or fluid-like network state to a contractile or solid-like state.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…properties and the formation of much smaller bipolar filament ensembles of only 10-20 motors 302 (Erdmann et al, 2016). Clearly, in future it will be interesting to study if end-dwelling is also observed for 303 non-muscle myosin.…”
mentioning
confidence: 97%